Preparing for the worst - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
As bird flu continues to claim more human lives, the international community began taking concrete steps to head off what is now openly talked of as a possible pandemic..